Anterior Open Bite Closure Using Ortodontic Mini-Implants - Szuhanek Camelia; Popa Adelina (Journal of Dentistry And Oral Implants, 2016)
This case report describes the treatment of a dento-alveolar protrusion with anterior open bite. The 21-year old patient had a convex profile , class I dental malocclusion , anterior open bite of 4 mm and presented tongue thrust. The treatment plan was to insert two mini-implants for premolar intrusion along with the straight –wire fixed appliances. Tongue therapy was performed by myofunctional exercises. Using the absolute anchorage we were able to achieve our goals in a predictable manner without the use of orthognathic surgery or patient compliance . After the tongue thrust habit was removed we are confident that this is a stable result .
Keywords: mini-implants